Cingulate protein arginine methyltransferases 1 regulates peripheral hypersensitivity via fragile X messenger ribonucleoprotein - Wu, Cheng; Shang, Hui-Fang; Wang, Yong-Jie; Wang, Jing-Hua; Zuo, Zhen-Xing; Lian, Yan-Na; Liu, Li; Zhang, Chen; Li, Xiang-Yao (Frontiers in Molecular Neuroscience, 2023)
The deficit of fragile X messenger ribonucleoprotein (FMRP) leads to intellectual disability in human and animal models, which also leads to desensitization of pain after nerve injury. Recently, it was shown that the protein arginine methyltransferases 1 (PRMT1) regulates the phase separation of FMRP. However, the role of PRMT1 in pain regulation has been less investigated. Here we showed that the downregulation of PRMT1 in the anterior cingulate cortex (ACC) contributes to the development of peripheral pain hypersensitivity. We observed that the peripheral nerve injury decreased the expression of PRMT1 in the ACC; knockdown of the PRMT1 via shRNA in the ACC decreased the paw withdrawal thresholds (PWTs) of naïve mice. Moreover, the deficits of FMRP abolished the effects of PRMT1 on pain sensation. Furthermore, overexpression of PRMT1 in the ACC increased the PWTs of mice with nerve injury. These observations indicate that the downregulation of cingulate PRMT1 was necessary and sufficient to develop peripheral hypersensitivity after nerve injury. Thus, we provided evidence that PRMT1 is vital in regulating peripheral pain hypersensitivity after nerve injury via the FMRP.